2018
DOI: 10.1002/mdc3.12673
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Markers of Progression in Parkinson's Disease

Abstract: Background Parkinson's disease (PD) is the second‐most common neurodegenerative disorder after Alzheimer's disease; however, to date, there is no approved treatment that stops or slows down disease progression. Over the past decades, neuroimaging studies, including molecular imaging and MRI are trying to provide insights into the mechanisms underlying PD. Methods This work utilized a literature review. Results It is now becoming clear that these imaging modalities can provide biomarkers that can objectively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 129 publications
(250 reference statements)
1
8
0
Order By: Relevance
“…Consistent with previous studies, we found that Parkinson's disease is associated with changes in brain functional connectivity that not only includes motor and subcortical nuclei, but also default, visual and attention systems (Fling et al, 2014;Canu et al, 2015;Fasano et al, 2015;Gilat et al, 2017Gilat et al, , 2018Gratton et al, 2018;Strafella et al, 2018).. It has been hypothesized that these heteromodal systems are involved in execution of automatic, habitual movements affected by PD (Gilat et al, 2017).…”
Section: Motor But Also Higher Order Attention Systemssupporting
confidence: 90%
“…Consistent with previous studies, we found that Parkinson's disease is associated with changes in brain functional connectivity that not only includes motor and subcortical nuclei, but also default, visual and attention systems (Fling et al, 2014;Canu et al, 2015;Fasano et al, 2015;Gilat et al, 2017Gilat et al, , 2018Gratton et al, 2018;Strafella et al, 2018).. It has been hypothesized that these heteromodal systems are involved in execution of automatic, habitual movements affected by PD (Gilat et al, 2017).…”
Section: Motor But Also Higher Order Attention Systemssupporting
confidence: 90%
“…There currently is not yet a consensus in the field on which imaging measures have the greatest utility as biomarkers for clinical trials in AP. Recent systematic reviews on available neuroimaging biomarkers for diagnosis and progression of AP disclosed that despite a plethora of studies, these have not yet yielded sufficiently validated biomarkers for diagnosis and disease progression, especially in the early course of disease or newly recognized variants [27–30]. This is problematic not only for finding a consensus but also because standard performance measures for newly developed imaging biomarkers are missing.…”
Section: Challenges For Ascribing Utility Of a Neuroimaging Biomarkermentioning
confidence: 99%
“…In the last few years, functional connectivity (FC) during resting-state functional magnetic resonance imaging (rs-fMRI) has been used in Parkinson’s disease (PD) to study the neural mechanisms of various complications, such as cognitive impairment 1 3 and depression 4 7 . Recently, a number of studies have applied time-varying analysis methods for brain connectivity, also known as dynamic FC, in diverse populations 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%